(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article is about the history of origin and formation of the theory of management as a scientiﬁ c discipline. Industrial, scientiﬁ c and technical basis of qualitative transformation of the world facilitated origin and development of the theory of management, and later changed the social structure of the XX century. However, it should be remembered that management itself was shown in the ancient civilization of humankind. Consequently, the theoretical understanding and analysis of the history of origin and formation of management mind will give us comprehesive anwers to the following questions: What is the management? What is a meaning of the theory of management? If the theory of management is a scientiﬁ c discipline. Keywords: theory, management theory, management, society, social system, public relations, functioning, effectiveness, competition, schools of management, scientiﬁ c management.